2019
DOI: 10.3389/fpls.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Potato Virus Y Detection in Seed Potatoes Using Deep Learning on Hyperspectral Images

Abstract: Virus diseases are of high concern in the cultivation of seed potatoes. Once found in the field, virus diseased plants lead to declassification or even rejection of the seed lots resulting in a financial loss. Farmers put in a lot of effort to detect diseased plants and remove virus-diseased plants from the field. Nevertheless, dependent on the cultivar, virus diseased plants can be missed during visual observations in particular in an early stage of cultivation. Therefore, there is a need for fast and objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 49 publications
(50 reference statements)
0
70
0
Order By: Relevance
“…Only plants that were at least 2 full plants away from diseased instances (roughly 80 cm) were considered as candidates to ensure the same high degree of status certainty as the NAK. This mirrors the approach by [26] that used the same dataset to model potato disease.…”
Section: Sampling and Modelingmentioning
confidence: 83%
“…Only plants that were at least 2 full plants away from diseased instances (roughly 80 cm) were considered as candidates to ensure the same high degree of status certainty as the NAK. This mirrors the approach by [26] that used the same dataset to model potato disease.…”
Section: Sampling and Modelingmentioning
confidence: 83%
“…The approach used in this study is capable of detecting C. sepium plants of various sizes. Compared to other studies [8,19,22] that used a hood or artificial lighting for image acquisition, our study targets weed detection under uncontrolled environments. It is difficult to directly compare the performance of the developed model as different datasets and metrics are used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pound et al [18] demonstrated that using deep learning can achieve state-of-the-art results (> 97% accuracy) for plant root and shoot identification and localization. Polder et al [19] adapted an fully convolutional neural network (FCN) for potato virus Y detection based on field hyperspectral images. Specifically, for crop/weed detection and segmentation, Sa et al [20,21] developed WeedNet and WeedMap architectures to analyse aerial images from an unmanned aerial vehicle (UAV) platform.…”
mentioning
confidence: 99%
“…However, the distributions of the averaged NDVIs were largely overlapped. Figure 6a shows the estimated probability density distributions of the averaged NDVI for the two nitrogen treatments by using the kernel density estimate (KDE) [29]. In this study, the supervised machine learning analysis and figure plotting were performed in the Python version 3.7.2 software environment [45].…”
Section: The Averaged Ndvi Comparisonmentioning
confidence: 99%
“…Due to the mechanisms of ML models, they can learn from data and, based on the learning, they can make the best predictions [23]. In fact, significant work has been done in similar plant phenotyping analyses, such as predicting nutrient contents [24,25], estimating the plant field [26], accessing biotic or abiotic stresses [27], and classifying desired traits [28,29]. However, analyses of the distribution features of leaves using supervised ML models has rarely been conducted.…”
Section: Introductionmentioning
confidence: 99%